Long-Term Clinical and Immunological Impact of Severe COVID-19 on a Living Kidney Transplant Recipient – A Case Report - Qiu, Liru; Zhang, Ji; Huang, Yafei; Chen, Gen; Chen, Zhishui; Ming, Changsheng; Lu, Xia; Gong, Nianqiao (Frontiers in Immunology, 2021)
The long-term impact of COVID-19 on transplant recipients remains unknown. We describe the case of a 30-year-old male kidney transplant recipient from Wuhan, China that was treated for severe COVID-19 in February 2020. He suffered an acute lung and renal injury and required systemic treatment including adjustment of his immunosuppressant regime. He was followed up to 1-year after discharge. No chronic lung fibrosis or deterioration of his pulmonary function was observed. Despite COVID-19 mediated damage to his renal tubular cells, no transplant rejection occurred. His immunological profile demonstrated both cellular anti-SARS-CoV-2 reactivity and specific humoral immunity. This case will help guide clinical decision making for immunocompromised individuals that become infected with SARS-CoV-2.